MEDAN MAKNA AKTIVITAS TANGAN ‘MENYAKITI KEPALA’ DALAM BAHASA JAWA DI JEPARA DAN HUBUNGANNYA DENGAN KONSERVASI BAHASA DAERAH - Sholikhah, Nikmatus; Nur Nabilah Fauziyah; Malik Fahad (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The use of Javanese language has encountered some shifts that require language documentation as a form of language conservation for the youth. This research aims to collect and describe semantic fields and semantic components of lexemes related to an activity of hurting head using hand in Javanese language in Jepara regency. The researchers also attempt to illuminate the connection between the study of semantic field and an attempt to conserve local language in globalization era. The data of this study was collected through an interview with Javanese native speakers in Jepara. The findings suggest that there are 16 lexemes related to the activity of hurting head using hand in Javanese language. Those lexemes are classified into two fields, namely an activity of hurting head by hitting and pulling. Each of semantic fields is further described based on a diagnostic component. Based on the diagnostic components, this study discovers three components to distinguish each of lexemes: the part of the hand used for hurting, the direction of hand for hurting, and the part of the head being hurt. Besides language documentation purposes, this semantic field research can also be used as a reference in society and an attempt to preserve local languages from the threat of endangerment.